NURSE’S SAFETY ATTITUDES AS PERCEIVED BY GERIATRIC PATIENTS IN HOMECARE INSTITUTIONS: Received: 29th December 2020; Revised: 10th March 2021, 22nd March 2021; Accepted: 15th June 2021 - Tirazona, Manuela P; Penetrante, Anielyne G; Tiamson, Ronie M; Arbo, Kahlil Z; Martinez, Ma. Cecilia O; Sablas, Karen G (LIFE: International Journal of Health and Life-Sciences, 2021)
The corona virus pandemic this year has given everyone bizarre health situations and an incommensurate danger, especially to the geriatric patients’ health, living conditions, interrelationships and overall well-being (Adhikari et al., 2020). No one knows how long this will last or when it will stop; its spread has affected many lives especially geriatric patients living in homecare institutions. The purpose of this study is to determine the nurse’s safety attitudes in times of pandemic as perceived by the geriatric patients in home care institutions. Data were gathered using an adapted and modified questionnaire entitled, “Nursing Home Survey on Patient Safety” from the research study of Alvin C. Ogalesco and Janet B. Lim of the University of Texas, for whom the authors were asked permission for its use. The research results showed: that most of the geriatric patients were 60 to 69 years old, female, married, and stayed for 0 to 9 years in the homecare institution; a very much evident nurse’s safety attitudes was noted as perceived by the geriatric patients in terms of cognitive, affective and psychomotor aspects; and that there were significant differences between the nurse’s safety attitudes when the respondents were grouped according to their gender, civil status and length of stay in the institution. It was recommended that: geriatric patients should view old age as an opportunity for continuous development, satisfaction, and well-being; and that nurses must always carry with them their best safety attitudes while taking care of them, keeping in mind all these characteristics especially on critical times like the pandemic; they must also become more sensitive to the needs of the geriatric patients, focusing on counseling them to become aware of the necessary steps to avoid infection during the pandemic; accept their limitations and mental health management.